Drivers of Energy Security Risks in the European Union: Implications for Sustainable Energy Policy - Yenisehirlioglu, Emirhan; Tarla, Esma Gultekin; Bayat, Tayfur (Mdpi, 2026)
Energy security has become a strategic priority for ensuring sustainable economic development, particularly for European Union (EU) countries characterized by high external energy dependence. This study investigates the key drivers of energy security risks in selected EU countries over the period 1995-2018, focusing on economic growth, tourism expenditures, technological innovation, renewable energy consumption, and urbanization. The empirical analysis employs panel vector autoregression and a panel error correction model to examine short- and long-run causal dynamics, while the augmented mean group estimator captures cross-country heterogeneity. The findings indicate that economic growth is the primary short-run determinant of energy security risk, whereas all variables exert significant long-run effects. Country-level results reveal common patterns for growth, renewable energy consumption, and urbanization, but heterogeneous impacts for tourism and technological innovation. These results suggest that strengthening renewable energy adoption, promoting innovation, and supporting sustainable urban development can enhance long-term energy resilience. Overall, this study provides policy-relevant insights for designing sustainability-oriented energy strategies aligned with the European Union's climate transition goals.
Keywords: energy security; sustainable energy policy; European Union; renewable energy; technological innovation; urbanization; economic growth; panel data analysis; energy resilience